Analysis Of Social Media Use Among Students Using Approaches Statistics And Probability - Ecca Andini Naretawati; Arvita Tivanny Ellen; Nandia Triyusvita; Dias Puspita Anggareni; Purwadi Purwadi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Social media has become an important part of students' lives as a medium for communication, entertainment, and information seeking. This study aims to analyze social media usage patterns among university students using descriptive statistics and probability approaches. Data were collected through a survey of 30 students using Google Forms. The observed variables included gender, semester level, residence status, duration of social media usage, purpose of use, and Grade Point Average (GPA). The results showed that 76.67% of respondents were female and 50% were second-semester students. Furthermore, 63.33% of students used social media for more than eight hours per day, while entertainment was the primary purpose of use (50%). Probability analysis indicated that the likelihood of a student using social media for more than eight hours daily was 0.633. The findings suggest that social media has become a major necessity for students, requiring proper time management to avoid negative impacts on academic activities.